KAJIAN KETERPADUAN ANTAR MODA: SEBUAH ANALISIS AKSESIBILITAS TRANSPORTASI PUBLIK PADA LAYANAN FEEDER WIRA-WIRI SURABAYA - Supriyadi, Sagita Alfira; Pradana, Galih Wahyu (Universitas Negeri Surabaya, 2024)
By improving the quality of public transportation services, this research can help in proving how the influence of public transportation accessibility and intermodal integration on service quality of the Wira- Wiri Surabaya feeder service. The method used in this research is quantitative method with the help of smartPLS version 4.1.0.2. Data sampling was done through a questionnaire using purposive sampling technique with a total of 100 respondents selected based on certain criteria. The implications of the results of this study indicate that accessibility and intermodal integration have a positive effect on the quality of transportation services. Public transportation accessibility has a positive influence on service quality with a p-value of 0.000 <0.005. Then, intermodal integration has a positive influence on service quality, as evidenced by a p-value of 0.000 < 0.005. These results indicate that the intermodal integration of the Wira-Wiri Suroboyo feeder has made it easier for people to transfer to other modes of transportation they are aiming for. Important things to maximize the quality of feeder services, can be done with the following: (1) improving and enhancing the quality of connecting roads; (2) increasing the frequency of feeder arrivals, especially during peak hours; (3) socialization of ticket integration; (4) information on the location and access of other modes of transportation; (5) improving the Gobis application so that it can update tracking data in real-time; (6) improving the lighting and infrastructure of feeder stops; (7) improving the attractiveness of infrastructure and maintenance of bus stops and their surroundings.